The role of ICT in Arab spring movements - Mark I. Wilson; Kenneth E. Corey (Netcom)
Over the past 25 years, social movements have actively sought out and used new information and communication technologies (ICT), such as the Internet and mobile phones, to give voice to their concerns. The growth of access and use of ICT in the Middle East and North Africa provided resources for protesters and governments to influence political and social events. The widespread availability of the Internet and mobile phones to facilitate organization and action raises the research question of how ICT affects protest movements.